“La inversión en el sector agropecuario y su incidencia en el PIB sectorial, periodo: 2000-2015” - Martinez Reinoso, Blanca Rosa (2018)
Investment in the Agricultural Sector and its Impact on GDP sectoral, during the period: 2000-2015; The study focuses on the analysis of investment in agricultural activity that is a priority and the cross-cutting axis that drives sectoral economic growth and social welfare; Through the implementation of physical infrastructure, research, innovation and development and the formation of human capital with the purpose of promoting competitive national production. The research is made up of four chapters detailed as follow. The research is made up of four chapters detailed as follow: The introduction and approach to the problem and the objectives both general and specific researches. In the Theoretical Framework it has been organized into four units: In the next one part responds to the investment in agricultural sector, the concepts, principles and theories; The following section the incidence analyzes the impact of Gross Domestic Sectoral Product, strategies and policies for agricultural development and their contribution to economic growth and poverty reduction; The economic theories of agriculture and the economic growth of the productive sector were contrasted. In the methodology, it describes the method research, indicators of the agricultural and livestock, amounts of investment in the agricultural sector; The behavior of the Gross Domestic Product and the results of the estimation of the econometric model, using the linear regression model estimated by the ordinary least squares method. Was finalized describing the conclusions, based on the results of the research developed and the respective recommendations that will give importance in the subsequent researches.